Serious Violent and Sexual Offenders: The Use of Risk Assessment Tools in Scotland - Kemshall, Hazel (2002)
First paragraph: The report of the MacLean Committee on serious violent and sexual offenders (Scottish Executive, 2000) identified a need for further research into risk assessment and recidivism in relation to this group. In response to the MacLean Committee recommendations the Scottish Executive commissioned research on risk assessment tools in use in Scotland. The aim of this research is to provide an audit of risk assessment instruments currently in use with serious violent and sexual offenders, to describe how they are used and to assess progress with the validation of risk assessment instruments for use in Scotland